2016
DOI: 10.1111/imj.13221
|View full text |Cite
|
Sign up to set email alerts
|

Return to sender: the need to re‐address patient antibiotic allergy labels in Australia and New Zealand

Abstract: Background Antibiotic allergies are frequently reported and have significant impacts upon appropriate prescribing and clinical outcomes. We surveyed infectious diseases physicians, allergists, clinical immunologists and hospital pharmacists to evaluate antibiotic allergy knowledge and service delivery in Australia and New Zealand. Methods An online multi-choice questionnaire was developed and endorsed by representatives of the Australasian Society of Clinical Immunology and Allergy (ASCIA), Australasian Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 33 publications
(58 reference statements)
1
23
0
Order By: Relevance
“…Recent work by Romano et al demonstrated patients with cephalosporin allergy commonly tolerated a different cephalosporin of varied R1/R2 side chain. 39 A recent survey of allergists, immunologists, pharmacists and infectious diseases physicians in Australia identified significant knowledge gaps regarding antibiotic cross-reactivity and absence of skin testing diagnostics to confirm, 40 echoed in surveys from the US and UK. 4143 The older literature also suggests erroneously high rates of cross-reactivity between penicillins and cephalosporins (10–25%).…”
Section: Cross-reactivity and Cross-checking: The Importance Of Side Chmentioning
confidence: 99%
“…Recent work by Romano et al demonstrated patients with cephalosporin allergy commonly tolerated a different cephalosporin of varied R1/R2 side chain. 39 A recent survey of allergists, immunologists, pharmacists and infectious diseases physicians in Australia identified significant knowledge gaps regarding antibiotic cross-reactivity and absence of skin testing diagnostics to confirm, 40 echoed in surveys from the US and UK. 4143 The older literature also suggests erroneously high rates of cross-reactivity between penicillins and cephalosporins (10–25%).…”
Section: Cross-reactivity and Cross-checking: The Importance Of Side Chmentioning
confidence: 99%
“…So, as well as optimising individual patient outcomes, appropriate allergy labelling and de‐labelling has also become an antimicrobial stewardship issue . Antibiotic allergy testing is very helpful in both de‐labelling penicillin‐allergic patients and identifying real beta‐lactam allergies but is not always readily accessible, especially for hospital inpatients . This study aims to estimate the prevalence of AALs recorded in medical records in an Australian tertiary hospital over an 18‐week period that could be removed immediately (as inappropriate) as well as identifying those in whom it would be relatively safe to perform a direct re‐challenge with a drug provocation test (DPT) based upon clinical grounds.…”
Section: Introductionmentioning
confidence: 99%
“…In cancer patients, more than 83% of AALs can be removed via formal antibiotic allergy testing, with such “de-labeling” associated with a 10-fold increase in appropriate antibiotic prescribing [ 2 , 3 ]. Unfortunately, despite the value of such programs, more than 50% of clinicians report that formal allergy testing services are either not available to them or not accessible in a timely fashion [ 4 , 5 ]. There has been growing interest in the role of direct oral challenge in patients with low-risk penicillin allergies to help address the obstacles that prevent widespread access to formal skin prick testing programs.…”
mentioning
confidence: 99%